Improvement of the Organizational and Economic Mechanism of Financing in the Road Economy - PECHONCHYK, Taras I.; KONTSEVA, Valentyna V.; BEZUGLYI, Artem A. (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019, 2019)
The urgency of the issue studied is preconditioned by the need to improve the state of the road economy by increasing its funding by improving its organizational and economic mechanism. The purpose of the article is to improve the organizational and economic mechanism of financing in the road economy. A leading method of this issue researching is modeling, which allows to consider it as a process of purposeful and complete reorientation of the mechanism of financing the road economy to more advanced methods and models. It has been established that efficient allocation of financial resources in the road economy is ensured through an organizational and economic mechanism, which includes a complex of interdependent organizational and economic elements, as well as special management functions that will form the necessary financial support for road enterprises for improving the transport and operational condition of roads. The study showed that the current regulatory provision of organizational and functional system of road management in Ukraine provides for centralization of road network management. The article presents the organizational and economic mechanism of financing in the road economy of Ukraine. The model is aimed at scientists and researchers whose area of interest is the road industry and its funding system.